Islam is a foreign country American Muslims and the global crisis of authority - Grewal, Zareena (Nation of newcomers: immigrant history as American history, 2014)
Probing the competing obligations of American Muslims to the nation and to the umma (the global community of Muslim believers), Islam is a Foreign Country investigates the meaning of American citizenship and the place of Islam in a global age.